Case studies in private sector participation solid waste management. (Development effectiveness country briefs., 2017)
In most urban areas in the Pacific, solid waste management services are the responsibility of the municipal authorities, who finance the services through their own budgets, with only limited contributions from fees paid directly by users. The private sector has been involved in the Pacific solid waste sector for many years, providing waste collection and/or disposal services in Fiji, Papua New Guinea, Samoa, Solomon Islands, and Tonga.